A case study of teaching religion using the Second Life® - Cassola, Fernando (2012)
With all the social changes brought by the technology, also in the teaching/learning processes we need to adapt the traditional curricula to a brand new generation of students, who are perfectly aware of this digital world. According to this idea and based on some research that is being made in the educational field using didactic games and 3D platforms, can predict that those platforms will become the most common way to meet one another, both in distance learning and business. Therefore, we used one of the most common 3D platforms, the Second Life (SL), to study its use for religious teaching. For this purpose we carried out a case study, during 3 different lessons and involving 4 different grade classes. At the end students were asked to answer a questionnaire. The results obtained are quite positive showing a wide range of opportunities for future usage and implementation of this kind of 3D and virtual world material, such as Second Life.